Mechanical effect of different implant caput-collum-diaphyseal angles on the fracture surface after fixation of an unstable intertrochanteric fracture: A finite element analysis - Kim, Jung Taek; Jung, Chang Ho; Shen, Quan Hu; Cha, Yong Han; Park, Chan Ho; Yoo, Jun Il; Song, Hyung Keun; Jeon, Yongho; Won, Ye Yeon (Asian Journal of Surgery, 2019)
Background/Objective: The choice of implant is one of the most easily controllable factors affecting the outcome of intertrochanteric fractures. While most of the caput-collum-diaphysis (CCD) angles of the femur are within the range of 125° and 130°, there is a shortage of data on whether 125° or 130° implants are preferable. Thus, the present finite element analysis (FEA) aimed to compare the biomechanical effects on the fracture surface when using implants with different CCD angles where the anatomical CCD angle of the femur was between 125° and 130°. Methods: After establishing a finite element model of an unstable intertrochanteric fracture from the femur with a native CCD angle of 127.3°, proximal femoral nail antirotation (PFNA) models with CCD angles of 125° and 130° were virtually implanted to have the same position of screw tip, respectively. Results: In the one-leg stance during walking, when the implant with 130º CCD angle was used, the magnitude of compressive stress (1.61 and 2.12 MPa in the 130° and 125° model, respectively) was lower and the area of the fracture surface under tensile stress (55% and 5% in 130° and 125° model, respectively), the interfragmentary movements (40.9% more movement in 130° model), and the magnitude of bone deformation (23.5% more deformation in 130° model) were more than those of the 125° model. Conclusion: The intertrochanteric fracture fixed with PFNA with a 125º CCD angle revealed less interfragmentary movement on the fracture surface when the native CCD was an in-between angle in the FEA.
Keywords: Biomechanical Phenomena; Bone Screws; Diaphyses; Femur; Femur Head; Finite Element Analysis; Fracture Fixation, Internal; Fractures, Ununited; Hip Fractures; Humans; Finite element analysis; Fracture fixation; Hip fracture; Proximal femoral nail antirotation